Shedding Light on Metal‐Based Nanoparticles in Zebrafish by Computed Tomography with Micrometer Resolution. Issue 31 (22nd June 2020) - Cörek, Emre; Rodgers, Griffin; Siegrist, Stefan; Einfalt, Tomaz; Detampel, Pascal; Schlepütz, Christian M.; Sieber, Sandro; Fluder, Pascal; Schulz, Georg; Unterweger, Harald; Alexiou, Christoph; Müller, Bert; et al.
Abstract: Metal‐based nanoparticles are clinically used for diagnostic and therapeutic applications. After parenteral administration, they will distribute throughout different organs. Quantification of their distribution within tissues in the 3D space, however, remains a challenge owing to the small particle diameter. In this study, synchrotron radiation‐based hard X‐ray tomography (SRμCT) in absorption and phase contrast modes is evaluated for the localization of superparamagnetic iron oxide nanoparticles (SPIONs) in soft tissues based on their electron density and X‐ray attenuation. Biodistribution of SPIONs is studied using zebrafish embryos as a vertebrate screening model. This label‐free approach gives rise to an isotropic, 3D, direct space visualization of the entire 2.5 mm‐long animal with a spatial resolution of around 2 µm. High resolution image stacks are available on a dedicated internet page (http://zebrafish.pharma-te.ch ). X‐ray tomography is combined with physico‐chemical characterization and cellular uptake studies to confirm the safety and effectiveness of protective SPION coatings. It is demonstrated that SRμCT provides unprecedented insights into the zebrafish embryo anatomy and tissue distribution of label‐free metal oxide nanoparticles. Abstract : Detection of unlabeled nanoparticles within soft tissues is a challenge. In this work, metal‐based nanoparticles are synthesized, injected into the bloodstream of zebrafish embryos, and visualized by synchrotron radiation‐based hard X‐ray tomography (SRμCT). It is demonstrated that SRμCT provides unprecedented insights into zebrafish embryo anatomy. Label‐free, non‐destructive localization of nanoparticles in a vertebrate embryo at submicron resolution is achieved.